2019
DOI: 10.1007/s10695-019-00650-5
|View full text |Cite
|
Sign up to set email alerts
|

Bioenergetics of fish spermatozoa with focus on some herring (Clupea harengus) enzymes

Abstract: Herring (Clupea harengus) shows the unique behavior of reproductive biology in which spermatozoa remains in the surrounding media for extended periods. It is an excellent model for studying the malic enzyme (ME) and creatine kinase (CK) biochemical properties because of their high activity and variability of molecular isoforms. The specific activity of NAD-preferring ME in herring spermatozoa is the highest among other fish spermatozoa and is localized in its large mitochondrion. Two different CK isoforms, dim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 65 publications
0
10
0
Order By: Relevance
“…[ 34 ] Moreover, Aqua Sperm micromotors from African catfish have a naturally short lifetime probably due to an inadequate energy supply as fish sperms consume ATP very fast by dynein ATPase within the flagellar motile apparatus that drives sperm movement. [ 35 ]…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 34 ] Moreover, Aqua Sperm micromotors from African catfish have a naturally short lifetime probably due to an inadequate energy supply as fish sperms consume ATP very fast by dynein ATPase within the flagellar motile apparatus that drives sperm movement. [ 35 ]…”
Section: Resultsmentioning
confidence: 99%
“…[34] Moreover, Aqua Sperm micromotors from African catfish have a naturally short lifetime probably due to an inadequate energy supply as fish sperms consume ATP very fast by dynein ATPase within the flagellar motile apparatus that drives sperm movement. [35] Once the morphology and mobility of Aqua Sperm micromotors were evaluated, their interaction with the bacterial biofilm was studied. To perform these experiments, bacterial biofilms were prepared in Petri dishes for 24 h (see experimental details in the Materials and Methods section).…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, a decrease in the activity of metabolism-related enzymes was also detected in cryopreserved sperm, suggesting that cell membranes integrity and mitochondria function of sperm could be damaged by cryopreservation. In fish and other vertebrates, LDH catalyzes the interconversion of pyruvate and lactate [ 32 ]. It was reported that lactate plus pyruvate seems to be the most favorable substrate to maintain ATP concentration and physiological level of adenylate energy charge of sperm from African catfish ( Clarias gariepinus ) during long-term storage at 4 °C [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…Mitochondria are micro-organelle that responsible for many biological function as generating energy, Ca homeostasis and apoptosis. The number and shape of mitochondria vary according to the cell types, as the number increase in cells that required high energy like muscles and sperm flagella (Perchec et al 1995;Gronczewska et al,2019).…”
Section: Introductionmentioning
confidence: 99%
“…The Oxidative phosphorylation proposed to be crucial determinant of the motility of sperms (Singh Rajender a.et al ,2010). Previous studies propose that fertilizing capacity related to characteristics of progressive motility of sperms and the sperms motility depending on the content of ATP (Christen et al 1987;Perchec et al 1995;Gronczewska .et al ,2019).…”
Section: Introductionmentioning
confidence: 99%